Dampak Insentive Reward terhadap Kerja Karyawan di PT. Nungguan Biotek Indonesia Gending - Budik Kusworo (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2016)
This study identify and analyze the performance of employees in the sales department PT. Nungguan Biotek Indonesia Gending regarding how employees can work the best and the more over have a high motivation to get the job done in the presence of incentives. Then the study of demonstrate the significance of the effect of incentives on performance of employees. The descriptive analysis was used to analyze data that contains the distribution items of each variable,also a simple linear regression analysis and hypothesis testing. The result of simple linear regression and partial regression analysis demonstrated that influance simultaneous incentive variable (X) to employee performance (Y) indicated by the value of R Square equal to 0.266. This figure shows that the simultaneous variable incentives (X) used in the regression equation is to contribute to the employee’s performance (Y) 26.6%, while the remaining 73.4% is influenced by other variables such as leadership and others. It concluded that significant and positive of the effect of incentives partially on the performance of employees in the sales department PT. Nungguan Biotek Indonesia Gending.